Health and security nexus in Southeast Asia: collective securitisation - Nadirah Mohd Azmi (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article examines how the Association of Southeast Asian Nations (ASEAN) collectively securitised a non-traditional security issue. Securitisation theory provides a way for government policymakers to devote more attention and resources to issues that might otherwise be overlooked. Securitisation theory, however, is not without significant shortcoming. The framework only emphasises nation-state as the referent object and unit of analysis. By contrast, the characteristics of non-traditional security issue threats require a multilevel relationship, as national solutions are often inadequate. This study, therefore, highlights the process of securitising infectious diseases at the ASEAN level and identifying the types of health challenges that have been collectively securitised. This was done through triangulation of academic materials, ASEAN’s official statements and semi-structured elite interviews of the discourse on Southeast Asian health policy between 1967 and 2010. This study argues that only diseases with the potential of becoming a pandemic and threaten the stability of a region have been successfully securitised at the regional level. Additionally, collective securitisation has increase multilateral cooperation among the ASEAN member states.